Dampak Pendampingan Gizi Ibu terhadap Perubahan Pengetahuan Gizi dan Praktik Pemberian Makan Baduta: The Impact of Maternal Nutrition Education on Changes in Nutritional Knowledge and Feeding Practices for Children Under Two Years of Age - Nadzifatussya'diyah, Nadzifatussya'diyah; Marliyati, Sri Anna; Nurdiani, Reisi; Nasution, Zuraidah; Ekayanti , Ikeu; Ekayanti, Ikeu (Jurnal Ilmu Gizi dan Dietetik, 2025)
This study aims to evaluate the impact of maternal education on nutritional knowledge and feeding practices of children under two years old. This research consisted of 70 subjects using pre-experimental techniques with a one group pre-test & post-test design. The location of this research is Sukadamai Village, Dramaga District, Bogor Regency in January-March 2024. Mothers' knowledge, attitudes and practices before and after the intervention increased for the better. There were significant differences in protein nutrients (p=0.033) and iron (0.002) while for other nutrients (energy, fat, carbohydrates, calcium and vitamin A) there were no significant differences before and after the intervention (p>0.05). The nutritional status of children under two years old based on the WAZ, HAZ dan WHZ indices before and after the intervention was given was mostly in the normal category. There were no significant differences for all WAZ, HAZ and WHZ indices before and after the intervention (p>0.05).